2022-RA-185-ESGO Results after conservative surgery of stage II/III serous borderline ovarian tumors. (20th October 2022) - Gouy, Sebastien; Maria, Sophie; Maulard, Amandine; Scherier, Stephanie; Zaccarini, Francois; Pautier, Patricia; Leary, Alexandra; Genestie, Catherine; Chargari, Cyrus; Morice, Philippe
Abstract : Introduction/Background: The aim of this study was to assess the outcomes of a large series of patients treated conservatively for stage II or III serous borderline tumors of the ovary (SBOTs) with a long-term follow-up. Methodology: Patients with SBOTs and peritoneal implants, treated in or referred to our institution, were retrospectively reviewed. Outcomes of patients treated conservatively (preservation of the uterus and at least a part of one ovary) to promote subsequent fertility were specifically analyzed. Results: Between 1971 and 2017, 212 patients were identified and followed-up. Among these patients, 65 underwent conservative treatment; eight patients had invasive implants. Among patients treated conservatively, 38 (58%) patients recurred. Twenty-eight recurrences were observed under the form of borderline tumor on the spared ovary and/or noninvasive implants, but eight patients had a recurrence under the form of invasive disease. Compared with radical surgery, the use of conservative treatment (p < 0.0001) was a prognostic factor on disease-free survival (DFS), but without an impact on overall survival (OS). Nevertheless, three deaths occurred. Twenty-four pregnancies (13 spontaneous) were observed in 20 patients (29 patients wanted to become pregnant). Conclusion: In this series collecting the largest number of patients undergoing conservative surgery for stage II/III SBOTs, spontaneous pregnancies can be achieved after conservative treatment of advanced-stage disease, but the recurrence rate is high and three deaths were observed. These patients were spared their fertility but with a high rate of recurrence. Uncertainties regarding the safety of conservative treatment should be exposed to these patients.